A Tale of Two Cities and the French Revolution: Exploring the Historical Context of A Tale of Two Cities (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Tale of Two Cities is an 1859 history book by Charles Dickens, dating to London and Paris before and during the French Revolution. The novel tells the story of Doctor Manette of France, his 18-year imprisonment in Bastille in Paris and his release to live in London with his daughter Lucie, whom he had never met. The story is set against the conditions that led to the French Revolution and the Reign of Terror. The current paper aims to create interest in A Tale of Two Cities and the French Revolution.